Epithelial response to IFN‐γ promotes SARS‐CoV‐2 infection - Julian Heuberger; Jakob Trimpert; Daria Vladimirova; Christian Goosmann; Manqiang Lin; Rosa Schmuck; Hans‐Joachim Mollenkopf; Volker Brinkmann; Frank Tacke; Nikolaus Osterrieder; Michael Sigal (EMBO Molecular Medicine, 2021)
Abstract SARS‐CoV‐2, the agent that causes COVID‐19, invades epithelial cells, including those of the respiratory and gastrointestinal mucosa, using angiotensin‐converting enzyme‐2 (ACE2) as a receptor. Subsequent inflammation can promote rapid virus clearance, but severe cases of COVID‐19 are characterized by an inefficient immune response that fails to clear the infection. Using primary epithelial organoids from human colon, we explored how the central antiviral mediator IFN‐γ, which is elevated in COVID‐19, affects epithelial cell differentiation, ACE2 expression, and susceptibility to infection with SARS‐CoV‐2. In mouse and human colon, ACE2 is mainly expressed by surface enterocytes. Inducing enterocyte differentiation in organoid culture resulted in increased ACE2 production. IFN‐γ treatment promoted differentiation into mature KRT20+ enterocytes expressing high levels of ACE2, increased susceptibility to SARS‐CoV‐2 infection, and resulted in enhanced virus production in infected cells. Similarly, infection‐induced epithelial interferon signaling promoted enterocyte maturation and enhanced ACE2 expression. We here reveal a mechanism by which IFN‐γ‐driven inflammatory responses induce a vulnerable epithelial state with robust replication of SARS‐CoV‐2, which may have an impact on disease outcome and virus transmission.